2014
DOI: 10.2320/matertrans.m2014289
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Tin, Silver and Copper from Waste Pb-free Solder Using Hydrochloric Acid Leaching with Hydrogen Peroxide

Abstract: The waste lead (Pb)-free solder leaching process in hydrochloric acid (HCl) solution with hydrogen peroxide (H 2 O 2 ) followed by separation of copper (Cu) and tin (Sn) was investigated to separate tin, silver (Ag), and copper as an individual component from waste Pb-free solder. The dissolution of Sn increased with increasing temperature and HCl concentration. ) of Cu could be removed successfully from the leach solution with Sn under the following conditions; 30°C in temperature; 400 rpm in agitation speed;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Conventional oxidants have disadvantages such as NO x gas emission due to HNO 3 leaching [33][34][35][36], increase in reagent consumption due to instability of H 2 O 2 [37,38], and requirement of additional separation process due to the use of Fe 3+ [38][39][40]. These drawbacks could increase the capital and environmental costs as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional oxidants have disadvantages such as NO x gas emission due to HNO 3 leaching [33][34][35][36], increase in reagent consumption due to instability of H 2 O 2 [37,38], and requirement of additional separation process due to the use of Fe 3+ [38][39][40]. These drawbacks could increase the capital and environmental costs as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic solder consists of mainly tin alloy combined with lead, copper, bismuth, zinc, indium, antimony and silver 26,28,29) . Kim et al 29) reported that Sn 4+ ions can oxidize tin metal in chloride solution and make two stannous (Sn 2+ ) ions as given in eq.…”
Section: Resultsmentioning
confidence: 99%
“…The standard reduction potential of Cu is found to be 0.34 V [5,6], which indicates that Cu metal cannot be oxidized and dissolved by sulfuric acid. Additional oxidants such as Fe 3+ [7,8], O 2 [9], Cl 2 [10] and H 2 O 2 [11] or leaching media such as HNO 3 [12,13], HCl [14][15][16][17], and NH 3 [18,19] have been used to leach Cu metals. The leaching of Sb in sulfuric acid solution has rarely been investigated, and the solubility of Sb 2 O 3 or Sb 2 O 5 , which could be generated from the oxidation of Sb, was found to be low [20].…”
Section: Methodsmentioning
confidence: 99%